FRI0051 Early arthritis induces disturbances at bone nanostructural level reflected in decreased tissue hardness. (15th June 2017) - Vidal, B; Cascão, R; Finnilä, M; Lopes, I; Saarakkala, S; Zioupos, P; Canhão, H; Fonseca, J
Abstract : Background: Arthritis induces joint erosions and skeletal bone fragility. Objectives: The main goal of this work was to analyze the early arthritis induced events at bone tissue level. Methods: Eighty-eight Wistar rats were randomly housed in experimental groups, as follows: adjuvant induced arthritis (N=47) and a control healthy group (N=41). Rats were monitored during 22 days for the inflammatory score, ankle perimeter and body weight and sacrificed at different time points (11 and 22 days post disease induction). Bone samples were collected for histology, micro-CT, 3-point bending, nanoindentation and Fourier transformed infrared spectroscopy (FTIR) analysis. Blood samples were also collected for bone turnover markers and systemic cytokine quantification. Results: At bone tissue level, measured by FTIR analysis and nanoindentation, there was a reduction of the mineral and collagen content and of hardness in the arthritic group, associated with an increase of the ratio of bone concentric to parallel lamellae and of the area of the osteocyte lacuna. In addition, increased bone turnover and changes in the microstructure and mechanical properties were observed in arthritic animals, since the early phase of arthritis, when compared with healthy controls. Conclusions: Arthritis induces very early changes at bone tissue level characterized by decreased tissue hardness and of collagen and mineral content. These observations highlight the pertinence of immediate control of inflammation in the initial stages of arthritis. Disclosure of Interest: None declared